The use of current genotyping assay methods for Neisseria gonorrhoeae - M. V. Shpilevaya; O. A. Obraztsova; A. V. Chestkov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The review deals with up-to-date genotyping assay methods of Neisseria gonorrhoeae. The review covers the characteristics and features of each method, application areas of genotyping assay of Neisseria gonorrhoeae. The methods described enable to upgrade the diagnostication of gonococcal infection, predict its antibiotic resistance, trace the contagion and channels of the infection as well as study the processes of molecular evolution of the microorganism. Information obtained based on up-to-date N. gonorrhoeae genotyping assay methods can be used in developing the reproductive health strategy of the population.